Symptom prevalence and management in older adult patients in Lebanon. Issue 4 (August 2019) - Huijer, Huda Abu-Saad; Fares, Souha; Bejjani, Rachele; Dhaini, Suzanne; Noureddine, Samar; Ghusn, Husam
Abstract: Objective: The purpose of this study is to explore symptoms and the effectiveness of their management in older adult palliative care candidates in Lebanon. The aims of this study were to: (1) determine symptom prevalence in Lebanese older adults who qualify for palliative care; (2) identify the severity and distress of symptoms; (3) identify the prevalence of symptom management and its efficacy; and (4) explore the relationship between overall symptom burden and its correlates. Method: This study uses an observational cross-sectional design using convenience sampling ( N = 203) to recruit older adults qualifying for palliative care from three major medical centers in Lebanon. Result: The mean age of the sample was 78.61 years. The most prevalent symptoms were lack of energy (93.5%), worrying (83.2%), and pain (71.4%). Psychological symptoms had the highest mean scores, preceded only by the physical symptoms and lack of energy. The most treated symptoms were physical with pain having the highest treatment prevalence (91%). Although psychological symptoms were the most burdensome, they were poorly treated. Multiple regression analysis showed that symptom scores had significant positive associations with financial status, social functioning, and comorbidities; there was a negative association with age. Significance of results: Lack of energy and psychological symptoms were the most prevalent, with the latter having the highest mean total symptom scores. Treatment was poor for psychological symptoms and effective for physical ones. Associations were found between age, comorbidity, financial problems, social functioning, and total physical and psychological mean symptom burden scores. More attention needs to be given to psychological symptoms and their management among older adults receiving palliative care.